Research overview - Mazlina, Abdul Majid (Penerbit UMP, 2017)

(untitled)
Welcome to this course titles "’Research Overview”. This objective of this course is to provide a guide to postgraduate students as they embark on their research journey. In this introduction, we want to point out some features of learning about research overview and discuss how to use this report in research. As postgraduate students of UMP, students will be familiar with the idea of research being a multi-paradigm discipline: research does not have a single paradigm of interlinked theory and method. Presently there have been concerns on the philosophical basis of research and the choice of appropriate research methods. Research can be carried out in two main methods; qualitative and quantitative research strategy, thus we will be considering quantitative and qualitative approaches separately.